Music industry forms: the 75 most important documents for the modern musician - Feist, Jonathan (Berklle Press, 2014)
Organize and manage your music projects! Whether you are a performer, writer, engineer, educator, manager, or music maker, these time-tested charts, plots, diagrams, checklists, and agreements will help make your work easier and better. These forms will help you clarify your work, track critical details, and maintain quality control. Each one includes explanation about how it is used, a key to related symbols and terms, and any common variations. You will find forms for: * Performance, to help you book, organize, and manage concerts and gigs (stage plots, set lists, booking request sheets) * Touring (tour itinerary, checklist, assets inventory) * Technology, to help you manage recording sessions, track gear, and label media (archive sheets, mic input diagrams, take sheets) * Writing songs, compositions and film scores, supporting both creative and business dimensions of the work (split sheets, spotting notes, cue sheets) * Business, including agreements, project management tools, and financial management (booking sheets, tour budget, profit/loss form) * Teaching (audition rating sheet, practice log, lesson plan) Also included are different types of notation formats, and some tips for creating your own forms.